Pengaruh Pendidikan Matematika Realistik Terhadap Prestasi Belajar Matematika Dengan Kovariabel Bakat Numerik Pada Siswa Kelas V SD Gugus Banyuning - I Putu Suardipa; Ni Nyoman Lisna Handayani (Purwadita : Jurnal Agama dan Budaya, 2021)
This research aims to investigate the effect of realistic mathematic education implementation toward mathematic learning achievement with numerical aptitude covariable of fifth grade students cluster V Banyuning. The research was a quasi-experiment with Posttest-Only Control-Group Design. Research population was the entire fifth grade students of cluster V Banyuning which consisted of 136 students. Research results show that: First, there was a difference in mathematic learning achievement between students who followed realistic mathematic education and students who followed conventional learning model (F = 17.537 with p < 0.05). Second, there was a difference in mathematic learning achievement between students who followed realistic mathematic education and students who followed conventional learning model after numerical aptitude covariable was controlled (F= 23.440 with p<0.05). Third, there was a contribution of numerical aptitude of 29,7% toward students mathematic learning achievement. Keywords: learning achievement, numerical talent, realistic mathematic education